Hubungan Pengetahuan dengan Pecegahan Kaki Daibetik pada Penderita Diabetes Melitus - Harun Wahyudi; Fadhila Arienda Humaira (Pusat Riset dan Inovasi Nasional, 2024)
Diabetic ulcers are the most feared problem by diabetes mellitus patients because they have a negative impact on patients such as tissue death, wounds that are difficult to heal, foul smelling, reddish and black. The more severe the leg injury, the patient must undergo amputation. This problem causes disturbances in the individual's self-concept, especially self-esteem. In this case, the family has a significant role in determining the health status of individuals who experience illness or illness. Research objectives This literature review aims to find variables to be studied from various theories with problems to be studied as reference material in the discussion of research results. The method in this research is this study was obtained by searching for written sources in the National Library, Google Scholar, national journals and international journals that are relevant to the problems studied. Keywords used are family support, self-esteem and diabetic ulcers. The results showed that from the 5 journals obtained, the results obtained were that the five journals had a relationship between family support and self-esteem in diabetic ulcer patients.